Criminalising the purchase of sex : lessons from Sweden - Levy, Jay, 1985- (Abingdon, Oxon : Routledge, 2015)
'In 1999, Sweden criminalized the purchase of sex whilst simultaneously decriminalizing its sale. In so doing, it set itself apart from other European states, promoting itself as the pioneer of a radical approach to prostitution. What has come to be referred to as the Swedish model has now been proposed in the Scottish, French, and Finnish parliaments. This book establishes the outcomes of this law - and the narratives that justify it - upon the dynamics of Swedish sex work, and upon the lives of sex workers. Drawing on recent fieldwork undertaken in Sweden over several years, including qualitative interviewing and participant observation, Jay Levy argues that far from being a law to be emulated, the Swedish model has had many detrimental impacts, and has failed to demonstrably decrease levels of prostitution. Criminalizing the Purchase of Sex: Lessons from Sweden utilises a wealth of respondent testimony and secondary research to redress the current lack of academic discourse on this politically-charged and internationally relevant topic. This original and timely work will be of interest to sex worker rights organisations, policy makers and politicians, as well as researchers across a number of related disciplines, including law, sociology, criminology, and gender studies'--
Introduction : Sweden, a brief history of'The People's Home' -- Methodology -- The sexkopslagen : legal and discursive precedent -- Perceptions, understandings and constructions -- Levels and spaces of sex work in Sweden -- The Swedish model on service provision : the prostitution units and harm reduction -- The Swedish model on service provision : sex workers' experiences -- Compromised citizenship : outcomes of law, policy and discourse -- Conclusions : social exclusion in Sweden's'People's Home.'
Includes bibliographical references (pages 232-246) and index.
Keywords: Prostitution -- Sweden; Prostitution -- Law and legislation -- Sweden